2009
DOI: 10.1088/0022-3727/42/11/115006
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in critical current density by tuning damping constants of CoFeB for spin-torque-transfer switching

Abstract: Different capping layers were deposited on 2.5 nm Co72Fe8B20 to investigate their effects on damping constants and critical current density (JC0) for spin-torque-transfer switching. The damping constant of CoFeB is affected by the interfacial conditions and the spin-pumping effects. The Cu capping layer significantly suppresses intermixing and possesses the lowest damping constant of 0.009. The micromagnetic simulations reveal that the low damping constant of CoFeB may result in the nucleation of domains at lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
(24 reference statements)
3
14
0
Order By: Relevance
“…(1) and (2), I sw is proportional to aÁM s ÁH k eff , 8,10 while the thermal stability factor is also proportional to M s ÁH k eff . 8 It may thus be possible to use a low Gilbert damping constant to reduce I sw without changing D. 18 In initial studies, I sw was reported to decrease in proportion to a; 19,20 however, this effect of a on I sw was reported for DC currents. There have also been studies using currents with finite duration, 3,7,11,[13][14][15] which reported that I sw is inversely proportional to the pulse duration (t p ) and that the magnetization switching is affected by temperature during the current pulse.…”
mentioning
confidence: 99%
“…(1) and (2), I sw is proportional to aÁM s ÁH k eff , 8,10 while the thermal stability factor is also proportional to M s ÁH k eff . 8 It may thus be possible to use a low Gilbert damping constant to reduce I sw without changing D. 18 In initial studies, I sw was reported to decrease in proportion to a; 19,20 however, this effect of a on I sw was reported for DC currents. There have also been studies using currents with finite duration, 3,7,11,[13][14][15] which reported that I sw is inversely proportional to the pulse duration (t p ) and that the magnetization switching is affected by temperature during the current pulse.…”
mentioning
confidence: 99%
“…The low saturation magnetization of CoFeB, which can lead to a decrease in the critical current density for ST switching [8], is a consequence of both reduced layer thickness [9] and Ta capping layer presence [10]. The normalized magnetization curve, calculated for t MgO = 0.72 nm, is plotted versus the applied magnetic field in Fig.…”
Section: Static Hysteresis Loopsmentioning
confidence: 99%
“…However, for MTJs with sufficiently high TMR % , it has been predicted that enhancing TMR further, and thereby , would not result in considerable reduction because increased spin polarization would not lead to significantly stronger spin torques [18]. On the other hand, can be tuned by optimizing material compositions (intrinsic damping) or changing the capping layers adjacent to the free layer (extrinsic damping) without degrading TMR [19]. For the intrinsic contribution, it has been reported that lower damping constant of Fe-rich Co Fe B decreases in comparison to Co Fe B [20].…”
Section: A Effective Damping Constantmentioning
confidence: 99%